Relationships Between the School-Level and Classroom-Level Environment in Secondary Schools in South Africa - Aldridge, Jill; Fraser, Barry; Laugksch, R. (Foundation for Education Science and Technology, 2011)
We report research into associations between the school-level and classroom-level environment in science classrooms in South Africa. An instrument, developed to assess students’ perceptions of their classroom learning environment as a means of monitoring and guiding changes towards outcomes-based education, was administered to 2,638 Grade 8 science students from 50 classes in 50 secondary schools in Limpopo province. In addition, the teachers of each of the 50 classes responded to a questionnaire developed to assess factors in the school-level environment (such as the adequacy of resources, parental involvement and collegiality). The data collected using the two questionnaires were analysed to examine whether the environment created at the school level was linked to the likelihood of teachers successfully implementing outcomes-based education at the classroom level.